Boundaries and Beyond China's Maritime Southeast in Late Imperial Times - Chin-keong, Ng (NUS Press, 2017)
Using the concept of boundaries, physical and cultural, to understand the development of China's maritime southeast in late Imperial times, these linked essays by a senior scholar challenge the usual readings of Chinese history from the centre. It looks at the challenges to such demarcations posed by movements of people, goods and ideas across maritime East Asia and the broader Asian Seas, and builds a fresh understanding of China's boundaries.Of interest to students of migration, of Chinese history, and of relations between China and its region, Ng's analysis provides crucial background to understanding China within Asia's maritime world. The result is a novel way of approaching Chinese history, argued from a fresh perspective on China's relations with neighbouring territories, and of the nature of tradition and its persistence in a changing world.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: History / Asia / China; History; History; Electronic books